An Analysis of Operational Risk Management in the Appointment Process of School Principals at Foundation X Based on ISO 31000:2018 - Songa, Apner; Rajagukguk, Wilson; Tewu, Denny (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Risk management is essential in educational governance to ensure the sustainability and quality of learning services. This study analyzes operational risks in the appointment process of school principals at Foundation X in North Maluku using the ISO 31000:2018 framework. The research applies a descriptive qualitative method through in-depth interviews, observations, and document analysis. The findings reveal that the principal appointment process has not yet been supported by standardized and documented procedures, opening space for subjective intervention, the dominance of informal power structures, and limited transparency in decision-making. The risk assessment identifies three high-priority risks: intervention from the Board of Trustees in principal selection, non-meritocratic appointments that disregard competency standards, and internal organizational conflicts stemming from weak leadership legitimacy. The application of ISO 31000:2018 enables systematic mapping of risk likelihood and impact, as well as the formulation of governance-oriented mitigation strategies such as the development of formal selection SOPs, the formation of an independent selection committee, and the reinforcement of performance evaluation mechanisms. This study contributes to improving risk management practices in foundation-based educational institutions by offering recommendations that promote transparency, accountability, and leadership quality.